2019
DOI: 10.1136/rapm-2018-100152
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the innervation of glenohumeral and acromioclavicular joint capsules: implications for image-guided intervention

Abstract: Background and objectivesIn 2011, chronic shoulder joint pain was reported by 18.7 million Americans. Image-guided radiofrequency ablation has emerged as an alternative intervention to manage chronic shoulder joint pain. To optimize the effectiveness of shoulder denervation, it requires a detailed understanding of the nerve supply to the glenohumeral and acromioclavicular joints relative to landmarks visible with image guidance. The purpose of this cadaveric study was to determine the origin, course, relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 34 publications
0
74
0
Order By: Relevance
“…innervation. Contrary to earlier belief that the suprascapular nerve innervates 70% of the shoulder joint, 11 recent anatomical studies 4,12 indicated that its contribution is modest and confined to the posterior superior quadrant of the joint. The C5 and C6 nerve roots that form the brachial plexus superior trunk (C5-C6) are major contributors to all of the axillary, subscapular, and suprascapular nerves.…”
mentioning
confidence: 72%
“…innervation. Contrary to earlier belief that the suprascapular nerve innervates 70% of the shoulder joint, 11 recent anatomical studies 4,12 indicated that its contribution is modest and confined to the posterior superior quadrant of the joint. The C5 and C6 nerve roots that form the brachial plexus superior trunk (C5-C6) are major contributors to all of the axillary, subscapular, and suprascapular nerves.…”
mentioning
confidence: 72%
“…The remaining shoulder joint areas are innervated by the SSN, which must be blocked in combination with the AN if complete anesthesia of the shoulder is to be achieved (see Aszmann et al, for the shoulder innervation and Price, for the clinical basis of the combined approach). The LPN, which lies in the interpectoral space (Blanco, ), contributes to the innervation of both the shoulder joint capsule and the acromioclavicular joint (Wrete, ; Aszmann et al, ; Tran et al, ). The injection of anesthetic drugs into the interpectoral space, called the Pecks blockade, is a safe technique for pain control in breast surgery and some of its variants can reach the LPN with minimal involvement of other nerves (Blanco, ; Pérez et al, ; Versyck et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated contribution of the AN to the totality of the shoulder joint innervation is variable. Near the quadrangular space, the main trunk gives direct articular branches to the inferior area (see also Tran et al, ) of the shoulder joint capsule, with other articular branches arising from the branch to the teres minor or appearing in the posterolateral aspect of the capsule after piercing the connective tissue of the tendon of the BB (Nasu et al, ; Eckmann et al, ). Some authors mention a single articular branch (Duparc et al, ), which they call the joint nerve (JN), while others use more general terms such as articular branch or capsular branch.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Anatomically, it is classically believed that 70% of shoulder glenohumeral joint innervation is provided by the suprascapular nerve; hence, blocking this nerve provides partial pain relief following shoulder surgery [34,35]. The remaining 30% of the joint is innervated by the axillary and subscapular nerves [34][35][36]. However, shoulder surgery is not only limited to the joint per se but it also involves the surrounding muscular and cutaneous tissues which derive additional innervation from the supraclavicular and pectoral nerves [37].…”
Section: Discussionmentioning
confidence: 99%